Reconstruction Compression Correlation Demodulation for Raman Optical Time Domain Reflection. Issue 10 (31st July 2021) - Li, Jian; Zhou, XinXin; Yin, Zitong; Wang, Chenyi; Xu, Yang; Zhang, Jianzhong; Zhang, Mingjiang
Abstract : A novel optical mechanism and scheme of Raman optical time domain reflection (ROTDR) for improving achievable spatial resolution is proposed. Herein, the Raman backscattering characteristic of the optical fiber based on the amplified spontaneous emission (ASE) detection is first theoretically analyzed. Then, the propagation model of the ASE Raman anti‐Stokes trace is established. Based on the propagation model, the time domain difference reconstruction is applied to the whole collected Raman anti‐Stokes trace. The reconstructed Raman anti‐Stokes signal and ASE signal, which are first proposed here, show a distinct correlation characteristic. For this characteristic, a higher signal‐to‐noise ratio (SNR) demodulation scheme, named compression correlation demodulation, is used to detect the temperature change along the optical fiber. The positive correlation peak generated by the proposed mechanism produces a multiplied amplification effect through compressing the whole intensity points of Raman anti‐Stokes in the fiber under test (FUT) region. Furthermore, the proposed scheme reduces the crosstalk of the non‐FUT in the demodulation process. Benefiting from this new optical sensing mechanism and scheme, a simulation experiment with 7.5 mm spatial resolution and 0.1 °C temperature sensitivity is demonstrated, and the spatial resolution is independent of sensing distance. These advances greatly facilitate the practicability of ROTDR. Abstract : Reconstruction compression correlation demodulation Raman optical time domain reflection (ROTDR) scheme for improving the achievable spatial resolution is proposed. A spatial resolution of 7.5 mm is obtained in the simulation results. This represents the ROTDR, ensuring the best spatial resolution. It provides real‐time distributed measurement for many potential applications, e.g., monitoring of large infrastructure.